Weakening of Nonlinear ENSO Under Global Warming - Tsubasa Kohyama; Dennis L. Hartmann; David S. Battisti (Geophysical Research Letters)
Abstract The amplitude response of the El Niño–Southern Oscillation (ENSO) to global warming is examined in two global climate models with realistic ENSO nonlinearity. Geophysical Fluid Dynamics Laboratory Earth System Model Version 2M (GFDL‐ESM2M) and Model for Interdisciplinary Research on Climate version 5 (MIROC5) are the two models that exhibit realistic ENSO nonlinearity. With quadrupled atmospheric carbon dioxide, the ENSO amplitude of GFDL‐ESM2M decreases by about 40%, whereas that of MIROC5 remains almost constant. Because GFDL‐ESM2M exhibits stronger climatological thermal stratification than MIROC5, greenhouse gas forcing increases the upper ocean stability and causes the thermocline to be less sensitive to wind perturbations. The stiffer thermocline inhibits the nonlinear variations of sea surface temperature so that the ENSO amplitude substantially weakens. Idealized nonlinear recharge oscillator model experiments further support climatological thermal stratification as a determinant of the warming response. Observations exhibit stronger thermal stratification than both models, which suggests that the real world may terminate strong, nonlinear El Niños sooner than model‐based projections.